Physicochemical and Pharmacokinetic Profiles of Gadopiclenol: A New Macrocyclic Gadolinium Chelate With High T1 Relaxivity. Issue 8 (August 2019) - Robic, Caroline; Port, Marc; Rousseaux, Olivier; Louguet, Stéphanie; Fretellier, Nathalie; Catoen, Sarah; Factor, Cécile; Le Greneur, Soizic; Medina, Christelle; Bourrinet, Philippe; Raynal, Isabelle; Idée, Jean-Marc; et al.
Abstract: Objectives: We aimed to evaluate gadopiclenol, a newly developed extracellular nonspecific macrocyclic gadolinium-based contrast agent (GBCA) having high relaxivity properties, which was designed to increase lesion detection and characterization by magnetic resonance imaging. Methods: We described the molecular structure of gadopiclenol and measured the r1 and r2 relaxivity properties at fields of 0.47 and 1.41 T in water and human serum. Nuclear magnetic relaxation dispersion profile measurements were performed from 0.24 mT to 7 T. Protonation and complexation constants were determined using pH-metric measurements, and we investigated the acid-assisted dissociation of gadopiclenol, gadodiamide, gadobutrol, and gadoterate at 37°C and pH 1.2. Applying the relaxometry technique (37°C, 0.47 T), we investigated the risk of dechelation of gadopiclenol, gadoterate, and gadodiamide in the presence of ZnCl2 (2.5 mM) and a phosphate buffer (335 mM). Pharmacokinetics studies of radiolabeled 153 Gd-gadopiclenol were performed in Beagle dogs, and protein binding was measured in rats, dogs, and humans plasma and red blood cells. Results: Gadopiclenol [gadolinium chelate of 2, 2′, 2″-(3, 6, 9-triaza-1(2, 6)-pyridinacyclodecaphane-3, 6, 9-triyl)tris(5-((2, 3-dihydroxypropyl)amino)-5-oxopentanoic acid); registry number 933983-75-6] is based on a pyclen macrocyclic structure. Gadopiclenol exhibited a very high relaxivity in water (r1 = 12.2 mM −1 ·s −1 at 1.41 T), and the r1 value in human serum at 37°C did not markedly change with increasing field (r1 = 12.8 mM −1 ·s −1 at 1.41 T and 11.6 mM −1 ·s −1 at 3 T). The relaxivity data in human serum did not indicate protein binding. The nuclear magnetic relaxation dispersion profile of gadopiclenol exhibited a high and stable relaxivity in a strong magnetic field. Gadopiclenol showed high kinetic inertness under acidic conditions, with a dissociation half-life of 20 ± 3 days compared with 4 ± 0.5 days for gadoterate, 18 hours for gadobutrol, and less than 5 seconds for gadodiamide and gadopentetate. The pharmacokinetic profile in dogs was typical of extracellular nonspecific GBCAs, showing distribution in the extracellular compartment and no metabolism. No protein binding was found in rats, dogs, and humans. Conclusions: Gadopiclenol is a new extracellular and macrocyclic Gd chelate that exhibited high relaxivity, no protein binding, and high kinetic inertness. Its pharmacokinetic profile in dogs was similar to that of other extracellular nonspecific GBCAs.